1999
DOI: 10.3109/02770909909055420
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Asthma and Other Childhood Allergies in Brazilian Schoolchildren

Abstract: We determined the prevalence of asthma, rhinitis, and eczema among Brazilian children using the standardized protocol of the International Study on Asthma and Allergies in Childhood (ISAAC) to facilitate the comparison of our results with other studies using the ISAAC methodology. We conducted a cross-sectional study from June to October 1994 to determine the prevalence of asthma, rhinitis, and eczema in 5182 school children aged 7-8 years and 13-14 years residing in the Brazilian towns of Santa Maria and Itab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
5

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 23 publications
0
10
0
5
Order By: Relevance
“…By looking at the data separately, we may see that the prevalence ranged from 4.8% in Itabira to 21.9% in Porto Alegre, in those individuals aged 13-14 years. [4][5][6][7] A cross-sectional study done with schoolchildren in Rio de Janeiro showed a prevalence of 21.7% for asthma according to the criteria of the questionnaire used (modified ATS-DLD-78 C). 8 Childhood asthma is a multicausal disease that has been associated with genetic, environmental, gestational and socioeconomic factors, among others, in several studies with children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…By looking at the data separately, we may see that the prevalence ranged from 4.8% in Itabira to 21.9% in Porto Alegre, in those individuals aged 13-14 years. [4][5][6][7] A cross-sectional study done with schoolchildren in Rio de Janeiro showed a prevalence of 21.7% for asthma according to the criteria of the questionnaire used (modified ATS-DLD-78 C). 8 Childhood asthma is a multicausal disease that has been associated with genetic, environmental, gestational and socioeconomic factors, among others, in several studies with children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…In Itabira and Santa Maria, cities in Minas Gerais state, a reported prevalence of asthma of 4.6% was observed in schoolchildren. 12 Chatkin,8 found a prevalence of 25.4% in a cohort from the city of Pelotas in 1997-98.…”
Section: Introductionmentioning
confidence: 99%
“…¦ Excluindo-se os não respondidos: prevalência = 19,7% (IC de 95%: 18,3-21,1%). ¶ Excluindo-se os não respondidos: prevalência = 19,4% (IC de 95%: 17,[9][10][11][12][13][14][15][16][17][18][19][20]9). ** Considerando-se o total dos dois períodos e excluindo-se os não respondentes: χ 2 de Pearson, p < 0,001.…”
Section: Métodounclassified
“…Camargos et al 11 , estudando adolescentes de 13 e 14 anos no interior de Minas Gerais, encontraram uma prevalência cumulativa de 27% de asma referida. Em Itabira e Santa Maria, cidades mineiras, observou-se uma prevalência de asma referida de 4,6% em escolares 12 . Em uma coorte na cidade de Pelotas, em 1997-98, Chatkin 8 encontrou uma prevalência de 25,4%.…”
Section: Introductionunclassified